2020
DOI: 10.3168/jds.2019-17219
|View full text |Cite
|
Sign up to set email alerts
|

Feeding colostrum or a 1:1 colostrum:milk mixture for 3 days postnatal increases small intestinal development and minimally influences plasma glucagon-like peptide-2 and serum insulin-like growth factor-1 concentrations in Holstein bull calves

Abstract: This study evaluated how feeding colostrum-or a colostrum-milk mixture for 3 d postnatal affects plasma glucagon-like peptide-2 (GLP-2), serum insulin-like growth factor-1 (IGF-1), and small intestinal histomorphology in calves. Holstein bulls (n = 24) were fed colostrum at 2 h postnatal and randomly assigned to receive either colostrum (COL), whole milk (WM), or a 1:1 COL:WM mixture (MIX) every 12 h from 12 to 72 h. A jugular venous catheter was placed at 1 h postnatal to sample blood frequently for the durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 68 publications
5
48
3
4
Order By: Relevance
“…Collectively, these results highlight several important notions. First, given that all calves within the current study rapidly surpassed FPT thresholds, we are confident that results within this study and companion studies (Inabu et al, 2019;Pyo et al, 2020) are not confounded by inadequate PT between treatments. Second, our data showed that serum IgG >20 g/L can be achieved early on, supporting the use of higher thresholds to determine adequate PT (Furman-Fratczak et al, 2011;Chigerwe et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Collectively, these results highlight several important notions. First, given that all calves within the current study rapidly surpassed FPT thresholds, we are confident that results within this study and companion studies (Inabu et al, 2019;Pyo et al, 2020) are not confounded by inadequate PT between treatments. Second, our data showed that serum IgG >20 g/L can be achieved early on, supporting the use of higher thresholds to determine adequate PT (Furman-Fratczak et al, 2011;Chigerwe et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
“…In addition, the colostral bioactive fraction is critically important in promoting gastrointestinal tract development (Bühler et al, 1998;Blättler et al, 2001;Steinhoff-Wagner et al, 2014) and possibly modulating neonatal metabolism from the absorption of hormones such as insulin (Pierce et al, 1964;Kirovski et al, 2008), leptin, or adiponectin (Kesser et al, 2015;Liermann et al, 2020). Regarding TM or part-colostrum mixtures, preliminary data indicate that these do positively affect the metabolic and hormonal profiles of neonatal calves (Inabu et al, 2019;Pyo et al, 2020). It is also very clear that TM, colostrum-milk mixtures, or prolonged colostrum feedings promote gastrointestinal development (Yang et al, 2015;Pyo et al, 2020), although the degree of gastrointestinal development with TM or colostrum-milk mixture feeding appears to be equivalent to prolonged colostrum feeding only when an initial meal of colostrum is provided (Yang et al, 2015;Pyo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The milking number affects a great amount of milk proteins; the majority of the 78 proteins are encompassed within catalytic activity, binding, cellular process. Therefore, rethinking the opportunity of feeding transition milk to calves at arrival and evaluating its impact on gut restoration rather than discarding this transition milk seems to be a good opportunity that needs to be explored as recently proposed by Pyo et al [ 90 ].…”
Section: Considerations To Advance In Future Nutritional Strategiementioning
confidence: 99%